EUS-FNA for a Pancreatic Neuroendocrine Tumor in a Four-Year-Old Daughter of a Woman Exposed to Radiation at Chernobyl. (17th June 2012) - Lachter, Jesse; Arkovitz, Marc S.; Postovski, Sergey; Waldner, Julian M.; Shaoul, Ron; Ishay, Offir Ben; Kluger, Yoram
Abstract : Pancreatic neoplasms in children are rare. Herein is reported the case of a four-year-old girl whose mother was exposed to radiation at Chernobyl that presented with obstructive jaundice and a mass suspected on CT and diagnosed by endoscopic ultrasound (EUS) with fine needle aspiration (FNA). This child is probably the youngest case of application of linear EUS with biopsy to be described. The diagnosis, management, and followup of children with this rare tumor are discussed.